Efficacy and safety of varenicline and bupropion, in combination and alone, for alcohol use disorder: a randomized, double-blind, placebo-controlled multicentre trialResearch in context - Bo Söderpalm; Helga Lidö; Johan Franck; Anders Håkansson; Daniel Lindqvist; Markus Heilig; Joar Guterstam; Markus Samuelson; Barbro Askerup; Cecilia Wallmark-Nilsson; Andrea de Bejczy (The Lancet Regional Health. Europe)
Summary: Background: Alcohol use disorder (AUD) is associated with an enormous burden of disease and cost to society. The dopamine deficiency hypothesis posits that negative reinforcement generated by a low brain dopamine state drives ethanol intake. Here, we evaluated the efficacy and safety of combined administration of two dopamine-enhancing drugs, varenicline (a partial nicotinic acetylcholine receptor agonist) and bupropion (a weak dopamine-reuptake inhibitor) on alcohol intake in AUD. Methods: Participants aged 25–70 years with moderate-to-severe AUD (defined as ≥4/11 Diagnostic and Statistical Manual of Mental Disorders [DSM]-5 criteria) were enrolled in this randomized, double-blind, placebo-controlled trial, done at four outpatient clinics in Sweden. Participants were randomly assigned (block size 8) 1:1:1:1 to Placebo + Placebo, Varenicline + Bupropion, Varenicline + Placebo, or Placebo + Bupropion. After a 1-week titration period, Varenicline was taken as 1 mg orally twice per day and bupropion as 150 mg orally twice per day for 12 weeks. Participants, investigators, and all study personnel were unaware of treatment allocation. The two primary outcomes were phosphatidylethanol in blood (B-PEth) and self-reported percentage heavy drinking days (%HDD), assessed over a steady state 10-week-period (from start of week 2 to end of week 11). Modified intention-to-treat (mITT) and per protocol analyses (PP) were performed using a sequential hierarchical statistical method. This registered study (EudraCT 2018–000048-24; clinicaltrials.gov NCT04167306) is completed. Findings: Between March 4, 2019, and December 14, 2022, 384 participants were randomly assigned: Placebo + Placebo = 97, Varenicline + Bupropion = 100, Varenicline + Placebo = 96, Placebo + Bupropion = 91. 72% participants were male (277/384) and 28% female (107/384), median age 57 (13) years. In the mITT analyses, Varenicline + Bupropion reduced B-PEth (Cohen's d [d] = 0·39, p = 0·004) and %HDD (d = 0·31, p = 0·008) vs Placebo + Placebo. Varenicline + Placebo also reduced B-PEth (d = 0·30, p = 0·005) and %HDD (d = 0·36, p = 0·023) vs Placebo + Placebo. For both primary endpoints, differences between the Varenicline + Bupropion and Varenicline + Placebo groups were not statistically significant (B-PEth: d = 0·022, p = 0·97, %HDD: d = 0·027, p = 0·76), precluding further comparisons according to the statistical hierarchy. In PP analyses, both primary outcomes were reduced with Varenicline + Bupropion (d = 0·43 [B-PEth]; d = 0·41 [%HDD]) and Varenicline + Placebo (d = 0·29 [B-PEth]; d = 0·34 [%HDD]) compared with Placebo + Placebo. Nausea, the only safety concern, was more common in the Varenicline + Placebo group than in the Placebo + Placebo group (49/96 vs 11/97, p < 0·0001) and of longer median duration (45 (70) vs 10 (14·5) days, p = 0·001). Nausea incidence was lower in the Varenicline + Bupropion group vs Varenicline + Placebo (36/100 vs 49/96, p = 0·048) and of shorter median duration (16·5 (39·3) vs 45 (70) days, p = 0·010). Interpretation: Two brain dopamine elevating treatments (Varenicline + Bupropion; Varenicline + Placebo) reduce alcohol consumption compared with placebo alone. Effect sizes were largest when Varenicline and Bupropion were combined and compliance was high (PP-population). Bupropion reduced Varenicline-induced nausea. Varenicline + Bupropion or other mild dopamine enhancers should be further explored for treatment of AUD. Funding: This study was funded primarily by the Swedish Research Council.